Tuberculosis-related stigma and its determinants in Dalian, Northeast China: a cross-sectional study - Xu Chen; Liang Du; Ruiheng Wu; Jia Xu; Haoqiang Ji; Yu Zhang; Xuexue Zhu; Ling Zhou (BMC Public Health, 2021)
Abstract Background The stigma of tuberculosis (TB) poses a significant challenge to TB control because it leads to delayed diagnosis and non-adherence. However, few studies on TB-related stigma have been completed in China. The aim of the current study was to explore the status of TB-related stigma and its associated predictive factors among TB patients in Dalian, Northeast China. Methods An institution-based, cross-sectional survey was conducted among outpatients at Dalian Tuberculosis Hospital in Liaoning Province, Northeast China. Data were collected by using a questionnaire that measured TB-related stigma, treatment status, anxiety, social support, doctor-patient communication and so on. A multiple linear regression model was used to determine the predictors of TB-related stigma. Results A total of 601 eligible participants were recruited. The mean score for TB-related stigma was 9.07, and the median score was 10. The average scores for anxiety, social support and doctor-patient communication were 4.03, 25.41 and 17.17, respectively. Multiple linear regression analysis revealed that patients who were female (β = 1.19, 95% CI: 0.38–2.01, P < 0.05), had self-assessed moderate or severe disease (β = 1.08, 95% CI: 0.12–2.03 and β = 1.36, 95% CI: 0.03–2.70, respectively, P < 0.05), and had anxiety (β = 0.38, 95% CI: 0.30–0.46, P < 0.001) were more likely to have a greater level of TB-related stigma than their counterparts. However, a significantly lower level of TB-related stigma was observed in patients with good social support (β = − 0.25, 95% CI: − 0.33--0.17, P < 0.001) and doctor-patient communication (β = − 0.14, 95% CI: − 0.29--0.00, P < 0.05). Conclusions This study showed that stigma among TB patients was high. Targeted attention should be paid to female patients and patients with moderate or severe disease in TB stigma-related interventions. Moreover, the important role of social support and doctor-patient communication in reducing TB-related stigma should also be emphasized.